Fine design modeling technology and intelligent implementation of through-layer drilling - Pei QIN; Changbao LIAN; Xiyuan LI; Juzheng SUN; Yuanmin LUO (Meikuang Anquan)
In order to ensure the safety of coal mine production and further improve the ability of coal mine gas control, based on the theory of gas flow in coal seam, starting with the analysis of effective extraction radius of gas, a mathematical model is established to determine the key indexes of fine design layout control of through-layer holes. The computer modeling technology is used to carry out the fine checking calculation of the borehole, and the development of the fine intelligent design system for the borehole distribution design of the coal seam gas pre-pumping in the bottom layer of the coal mine is completed. The system can accurately perceive and independently check the borehole compound calculation in the given area, so as to realize the less human and fine drilling design process, and the analysis and comparison with the traditional design are carried out. The research shows that the use of fine intelligent drilling design can maximize the equal density distribution of the borehole axis in the coal body, and make the drilling project less than the traditional design. It can be seen that the intelligent design of massive floor through-layer drilling makes the drilling construction and coal seam gas extraction effect is good, the construction difficulty is reduced and the coal mine gas prevention and control ability and management level are significantly improved.